Report: Seventh Meeting of the IUCN/SSC African Elephant Specialist Group - Skinner, Diane (Pachyderm, 2010)
The IUCN/SSC African Elephant Specialist Group (AfESG) held its seventh meeting for members from 23–27 November 2009 at the KCB Leadership Centre in Nairobi, Kenya. The meeting was attended by many of AfESG’s members, as well as a number of observers and guest speakers who participated in some or all of the sessions. The agenda was tightly packed with technical presentations and working sessions on a variety of issues relating to African elephant conservation and management. The main themes are summarized in this report.